Trophic ecology of a tropical scyphozoan community in coastal waters: insights from stomach content and stable isotope analyses - Wan Mohd Syazwan; Then, Amy Yee Hui; Chong, Ving Ching; Idid, Mohammed Rizman (Elsevier, 2021)
Despite the growing concern of scyphozoan jellyfish blooms and their associated threats, there is an acute lack of baseline knowledge regarding the trophic ecology of scyphozoans in tropical waters where blooms of several species sometimes occur at once or successively. Therefore, this study was conducted from June 2010 to December 2011 in the Klang Strait (Malaysia) to elucidate the trophic ecology of eight sympatric species of scyphozoan that occurred in a conjoint mangrove-mudflat habitat. The species diet, trophic position and the relative contribution of primary producers to their nutrition were determined by integrating stomach content examination with stable isotope analysis. Scyphozoans in the Klang Strait are principally carnivores and can be grouped into three major trophic guilds: specialized copepod feeder, copepod and macrozooplankton feeder, and mixed plankton feeder. Bayesian mixing model of δ13C isotope values indicates that the scyphozoans mainly derived their basal carbon source from microphytobenthos and phytoplankton. Analysis of δ15N isotope values reveals that all species are positioned at the third trophic level after mixed zooplankton groups (second) and primary producers (first) in the food web. Scyphozoans thus represent an important trophic link coupling benthic and pelagic primary production to higher-level predators and humans, and are important carbon exporters from nearshore to neritic and offshore waters.